A Theoretical Study of Financial Literacy with Financial Analysis - Mijarul Islam; Pranam Dhar; Sandeep Poddar; Amiya Bhowmik, (International Journal of Management and Human Science (IJMHS), 2022)
The purpose of this paper is to analyse a fast-developing collection of economic research on financial literacy. We begin with a review of theoretical research that portrays financial knowledge as a sort of human capital investment. Indigenizing financial information has significant ramifications for welfare and programmes aimed at improving financial literacy in the general population. Then, using data from recent surveys, we determine how much (or how little) people know about money and identify the population segments with the least financial knowledge.